AVALIAÇÃO DOS NÚCLEOS DE INOVAÇÃO TECNOLÓGICA DO INSTITUTO FEDERAL DO PARANÁ - SÁ, CLAYTON PEREIRA DE (2020)
The NIT seeks to promote innovation and protection of the knowledge generated in the institution, as well as the process of technology transfer to the private sector. It is present in universities and research institutes, helping entrepreneurship and generating competitive advantage for Brazil. The management of the innovation process at the Federal Institute of Paraná is coordinated by the Innovation Agency (AGIF). The IFPR has twenty-six campuses and a reference center. The campuses are spread throughout the state, making management a complex activity. This study is an important tool to assist IFPR managers in the process of evaluating the policies developed by the institution. To support this research, the methodology employed uses applied, exploratory research with a qualitative and quantitative approach. The data collection comprises bibliographic and documentary research, with a view to identifying the guidelines and policies developed by the institution in literature and legislation. In the first stage, the bibliographic review was performed. The second stage of the research consisted of a documental research, laws and norms. Regarding the third stage, the questionnaire was applied to the NIT coordinators and AGIF managers. The fourth stage consisted of a survey on the INPI (National Institute of Industrial Property) website, in order to survey the protection requests made by the IFPR. After this survey, the Folha University Ranking (RUF) was consulted to verify the innovation indicators of public universities in the state of Paraná. The survey aims to evaluate the stages of implementation of essential activities in the NIT of the IFPR. Identify the innovation activities developed in the campuses, areas of activity and possible links between the innovations developed by the institution and the local professional aptitude, as well as the guidelines and objectives of the innovation policy that the institution has already implemented. As a result, it was possible to verify the innovation indicator called "Intellectual Production Rate" presented by IFPR and compare it with other public universities in the state of Paraná. Therefore, the product delivered is a report regarding the proposal or evaluation of programs, projects and institutional or public policies. Then, as a proposal, an instructional technical publication was prepared to support the NIT in the process of dissemination of knowledge on innovation and innovation management.